2014
DOI: 10.1007/s13577-013-0082-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multipotency and molecular profile of MSCs between CKD and healthy rats

Abstract: We previously showed that mesenchymal stem cells (MSCs) can differentiate into a functional miniature kidney, suggesting that MSCs may be a cell source for kidney regeneration. However, MSCs from long-term dialysis patients, which have been exposed to uremic toxin, can exhibit reduced viability. Therefore, the aim of this study was to examine the gene expression profiles and differentiation capabilities of bone marrow- and adipose-derived MSCs from chronic kidney disease (CKD) model rats. CKD was induced in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…Our present results support the observation that the isolated and expanded bone marrow-derived MSCs from ESRD patients and healthy controls are phenotypically similar [35]. It was found that CKD in model rats had a small effect on the gene expression and differentiation of MSCs [36]. However, long-term exposure to the uremic toxin may affect the surface marker and gene expression of MSCs derived from bone marrow and umbilical cord.…”
Section: Discussionsupporting
confidence: 89%
“…Our present results support the observation that the isolated and expanded bone marrow-derived MSCs from ESRD patients and healthy controls are phenotypically similar [35]. It was found that CKD in model rats had a small effect on the gene expression and differentiation of MSCs [36]. However, long-term exposure to the uremic toxin may affect the surface marker and gene expression of MSCs derived from bone marrow and umbilical cord.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, Dkk-1 expression was downregulated during the osteogenic differentiation of aortic myofibroblasts [44,48], which is in accordance with the gene expression profile of uremic pulp in the present study. Furthermore, previous studies have demonstrated that the regenerative capability of stem cells derived from CKD subjects was impaired [27,50], which is consistent with stem cell paucity observed in uremic pulp. Therefore, our results provide another evidence that stem cell perturbation plays an important role in uremic ectopic ossifications.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, aging and aging-related disorders significantly impair the survival and differentiation potential of bone marrow MSCs [38][39][40][41] . Bone marrow MSCs isolated from chronic heart disease patients and chronic kidney disease rat models displayed a reduced proliferation and differentiation capacity [41][42][43] , limiting their therapeutic efficacy.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%